Structural modelling of wellbeing for Indigenous Australians: importance of mental health - Rosalie Schultz; Stephen Quinn; Byron Wilson; Tammy Abbott; Sheree Cairney (BMC, 2019)
Abstract Background Australia provides health care services for Indigenous peoples as part of its effort to enhance Indigenous peoples' wellbeing. However, biomedical frameworks shape Australia's health care system, often without reference to Indigenous wellbeing priorities. Under Indigenous leadership the Interplay research project explored wellbeing for Indigenous Australians in remote regions, through defining and quantifying Indigenous people's values and priorities. This article aimed to quantify relationships between health care access, mental and physical health, and wellbeing to guide services to enhance wellbeing for Indigenous Australians in remote regions. Methods Indigenous and non-Indigenous researchers worked with Indigenous people in remote Australia to create a framework of wellbeing priorities. Indigenous community priorities were community, culture and empowerment; these interplay with government priorities for Indigenous development of health, education and employment. The wellbeing framework was further explored in four Indigenous communities through a survey which measured aspects of the wellbeing priorities. Indigenous community researchers administered the survey in their home communities to 841 Indigenous people aged 15 to 34 years from June 2014. From the survey items, exploratory factor analysis was used to develop constructs for mental and physical health, barriers to health care access and wellbeing. Relationships between these constructs were quantified through structural equation modelling. Results Participants reported high levels of health and physical health (mean scores (3.17/4 [SD 0.96]; and 3.76/4 [SD 0.73]) and wellbeing 8.07/10 [SD 1.94]. Transport and costs comprised the construct for barriers to health care access (mean access score 0.89/1 [SD 0.28]). Structural equation modelling showed that mental health, but not physical health was associated with wellbeing (β = 0.25, P < 0.001; β = − 0.038, P = 0.3). Health care access had an indirect positive relationship with wellbeing through mental health (β = 0.047, P = 0.007). Relationships differed significantly for participants in remote compared with those in very remote communities. Conclusions Greater attention to mental health and recognition of the role of services outside the health care sector may have positive impacts on wellbeing for Indigenous people in remote/ very remote Australia. Aggregation of remote and very remote populations may obscure important differences between Indigenous communities.